Prevalence and factors associated with dental erosion in individuals aged 12–30 years in a northeastern Brazilian city - Luciano LC; Ferreira MC; Paschoal MA (Dove Medical Press, 2017)
Luanda Cristina O Luciano,1 Meire Coelho Ferreira,2 Marco Aurelio Paschoal2 1Dentistry Program, Facimp Devry, Imperatriz, 2Post Graduate Program in Dentistry, CEUMA University, São Luís, Brazil Background/Purpose: Dental erosion in young individuals has increased significantly in recent years, due to changes in lifestyle. Thus, the present study investigated the prevalence and factors associated with dental erosion in individuals aged 12–30 years in the city of Imperatriz of Maranhão, Brazil.Materials and methods: A cross-sectional study was conducted on 335 individuals who answered a questionnaire consisting of variables related to dental erosion. Afterwards, the individuals were subjected to clinical examinations and the basic erosive wear examination index was used to classify their teeth according to the presence and severity of dental erosion.Results: Descriptive statistics, the chi-square test, Poisson univariate and multivariate regression were performed at 5% level of significance. The sample was characterized by 204 females (60.9%), the majority of whom were from 12 to 19 years of age (78.5%), among whom 28.7% presented dental erosion. Their monthly family income was from 1 to 3 minimum wages (56.4%). The variables that were significantly associated with the outcome were family income, chewing gum, and consumption of soft-drinks/juices before going to sleep (p=0.03, p=0.001, and p=0.04, respectively). Individuals who chewed chewing gum were 2.27 times (95% CI =1.43–3.60) more likely to present dental erosion than those who did not chew gum. Individuals who ingested soft drinks or juices were 2.30 times (95% CI =1.30–4.10) more likely to present dental erosion.Conclusion: The prevalence of erosion reflected the need for programs of prevention and guidance for patients about the etiological factors of the disease. Keywords: young adults, dental erosion, prevalence, factors, tooth wear, life style